2020
DOI: 10.35848/1347-4065/ab8b3c
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb-limited mobility in 4H-SiC MOS inversion layer as a function of inversion-carrier average distance from MOS interface

Abstract: The Coulomb-limited mobility (μ Coulomb ) of Si-face 4H-SiC MOSFETs with nitrided gate oxide is experimentally evaluated. μ Coulomb is experimentally determined using samples with various acceptor concentrations by varying the body bias. It is found that the depletion-charge and surface-carrier densities in the inversion layer can be utilized to well formulate μ Coulomb . In addition, μ Coulomb is investigated as a function of the inversion-carrier average distance from the MOS interface (Z AV ), and it is est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The μ FE /μ bulk ratio for both the n-and p-channel devices highly depends on E eff rather than N D,A , indicating the ionized impurities are not a dominant scattering center in both the n-and p-channel SiC MOSFETs with the nitrided gate oxides. As for the n-channel MOSFETs, it has been already reported that the ionized impurities may not dominate channel mobility, 40) and the present study revealed that the decrease in μ FE for heavily-doped SiC MOSFETs annealed in NO is not caused by ionized-impurity scattering but linked to the high E eff for both the n-and p-channel devices. Based on the result that D it near E c is higher than that near E v , scattering from trapped carriers in the p-channel devices should be weaker than that in the n-channel devices, and this may be the major reason why the μ FE /μ bulk ratio for the n-channel devices drops more sharply than that for the p-channel devices.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The μ FE /μ bulk ratio for both the n-and p-channel devices highly depends on E eff rather than N D,A , indicating the ionized impurities are not a dominant scattering center in both the n-and p-channel SiC MOSFETs with the nitrided gate oxides. As for the n-channel MOSFETs, it has been already reported that the ionized impurities may not dominate channel mobility, 40) and the present study revealed that the decrease in μ FE for heavily-doped SiC MOSFETs annealed in NO is not caused by ionized-impurity scattering but linked to the high E eff for both the n-and p-channel devices. Based on the result that D it near E c is higher than that near E v , scattering from trapped carriers in the p-channel devices should be weaker than that in the n-channel devices, and this may be the major reason why the μ FE /μ bulk ratio for the n-channel devices drops more sharply than that for the p-channel devices.…”
supporting
confidence: 60%
“…The major scattering mechanisms in heavily-doped MOSFETs include ionized-impurity scattering, scattering due to high E eff including roughness scattering, 32) and Coulomb scattering from fixed charges or trapped carriers near the SiO 2 /SiC interface. 40,41) To investigate the dominant scattering mechanisms in SiC MOSFETs, we applied a positive voltage to the body electrode of the p-channel devices to increase E eff while keeping the ionized-impurity (donor) density. In a similar manner, a negative body bias was applied to the n-channel devices to increase E eff .…”
mentioning
confidence: 99%
“…Therefore, for electrons, transport is limited by Coulomb and phonon scattering. From the trend of the experimental results in figure in Section 3.3 and other published results [ 23 , 26 ], electron mobility will reduce below 77 K due to increased Coulomb scattering. Above 373 K, mobility would also decrease, but due to increased phonon scattering.…”
Section: Resultsmentioning
confidence: 61%
“…The second cause is the low free electron mobility (µ free ) of the remaining mobile electrons in the MOS channel [8,9,[11][12][13][14][15][16]. It has been found that the high density of D it near E C can be reduced and thus the n free s can be improved [8][9][10].…”
mentioning
confidence: 99%
“…Owing to its technological importance, a number of detailed experimental studies on the µ free have been undertaken using Hall effect measurements [11][12][13][14][15][16]. We note that the experimental results regarding the mobility in MOSFETs are generally parameterized bt the Effective field (E eff ) in order to investigate the mobility-limiting scattering mechanisms [20][21][22][23].…”
mentioning
confidence: 99%